After-school centers and youth development : case studies of success and failure - Hirsch, Barton Jay, 1950-; Deutsch, Nancy L.; DuBois, David L. (Cambridge : Cambridge University Press, 2011)
'This book examines after-school programs, exploring how - and why - young people thrive in good programs and suffer in weak ones'--
'This book examines after-school programs in light of their explosive growth in recent years. In the rush to mount programs, there is a danger of promoting weak ones of little value and failing to implement strong ones adequately. But what is quality and how can it be achieved? This book presents findings from an intensive study of three after-school centers that differed dramatically in quality. Drawing from 233 site visits, the authors examine how - and why - young people thrive in good programs and suffer in weak ones. The book features engaging, in-depth case studies of each of the three centers and of six youths, two from each center. Written in a highly accessible style for academics, youth workers, after-school program leaders, and policy makers, the study breaks new ground in highlighting the importance of factors such as collective mentoring, synergies among different programs and activities, and organizational culture and practices. Guidelines are included for program improvement'--
Includes bibliographical references (p. 331-350) and index.
Keywords: After-school programs -- United States -- Case studies; Youth development -- United States -- Case studies; Student activities -- United States -- Case studies